Navigating Change: Assessing The Socio-Cultural Impact Of Garo Literary Contributions (Journal of Namibian Studies : History Politics Culture, 2023)
This study seeks the socio-cultural impact of Garo literary accomplishments in diverse cultural environment. The Garo, an ethnic group have coexisted peacefully with the society for decades, preserving their cultural identity despite continuous contact. The research aims to evaluate the transforming processes of Garo society, specifically in relation to evolving family structures and cultural customs, as impacted by their literary manifestations. Also, to analyze the evolution of Garo's traditional family structures and cultural practices, considering the impact of regular encounters with the mainstream population and the influence on the Garo family and cultural life. However, the significance of literature in documenting and mirroring socio-cultural changes within excluded populations. The study argues that while Garo society is experiencing slow changes, traditional norms and practices continue to have a significant impact on family structures and cultural life. The study highlights the importance of Garo literary accomplishments in understanding the socio-cultural influence of external contacts and cultural changes.